Immunodiagnostic profiling of SPON2 and MSMB as biomarkers in prostate cancer for nanomaterial- based detection strategies - Ye, Jianzeng; Zhong, Fuhua; Xia, Jinquan; Zeng, Jun; Fang, Zhiye (Frontiers in Immunology, 2025)
BackgroundThis study aimed to validate secreted biomarkers SPON2 and MSMB with tumor-specific expression and immunogenicity for nanomaterial-based prostate cancer diagnostics.MethodsGene expression data (GSE55945), comprising 13 prostate tumor and 8 normal tissue samples, retrieved from the GEO database and analyzed by Affymetrix Human Genome U133 Plus 2.0 Array platform. Differentially expressed genes (DEGs) were identified using thresholds of |log2 fold change| >1 and adjusted p < 0.05. Upregulated DEGs filtered for secretory proteins based on annotations from Human Protein Atlas and UniProt databases. Candidate genes were prioritized using receiver operating characteristic (ROC) analysis, selecting those with area under the curve (AUC) > 0.85 for validation. Quantitative reverse transcription PCR (qRT-PCR) was performed using clinical tumor and matched normal prostate tissues, with GAPDH as internal control. Extracellular accessibility and immune relevance of SPON2 and MSMB were evaluated for diagnostic translation. B cell epitope prediction was done using IEDB and VaxiJen tools to assess immunogenic potential. Selected peptide epitopes were synthesized and validated by indirect ELISA using sera from prostate cancer patients and healthy controls.ResultsOut of 243 DGE, five upregulated candidates encoding secretory proteins were identified. Of these, SPON2 and MSMB exhibited high diagnostic performance with AUC values of 0.99 and 0.93, respectively. qRT-PCR validation in clinical samples confirmed significant overexpression of SPON2 (~18-fold) and MSMB (~2.6-fold) in prostate tumor tissues compared to matched normal tissues. Both proteins demonstrate extracellular localization and immune accessibility, supporting their feasibility as targets for antibody- or epitope-based capture strategies. These properties position SPON2 and MSMB as ideal candidates for nanoparticle-conjugated peptide biosensors designed for immunomodulated detection of prostate cancer. Epitope E1 (SPON2) and E2 (MSMB) showed antigenicity scores of 0.80 and 0.52, respectively, and were validated by ELISA, with E1 exhibiting significantly higher reactivity in cancer sera (OD 1.49 vs. 0.81, p < 0.01; AUC 0.98) and E2 showing moderate discrimination (OD 1.27 vs. 0.87, p < 0.05; AUC 0.88).ConclusionSPON2 and MSMB are secretory, immunogenic biomarkers overexpressed in prostate cancer. Their validated B cell epitopes demonstrate strong diagnostic performance, supporting their potential in nanomaterial-based immunodiagnostic strategies for non-invasive prostate cancer detection.